2020
DOI: 10.1007/s00127-020-01879-9
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between perceived social support and cardiovascular health behaviours in people with severe mental illnesses?

Abstract: Purpose People with severe mental illnesses (SMI) have an increased risk of cardiovascular disease (CVD). Research in the general population suggests that social support may protect against increased CVD morbidity and mortality; however, this may not apply to those with SMI. We aimed to explore the association between perceived social support and attendance at primary care nurse CVD risk reduction clinic appointments and CVD risk-reducing behaviours in an SMI population with elevated CVD risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Consistent with previous research, social support was not associated with missing appointments, but this was somewhat unexpected. [37][38][39] Family support reduces relapse and improves clinical outcomes. [40] Our instrument may not have captured the specific aspects of social support crucial for treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous research, social support was not associated with missing appointments, but this was somewhat unexpected. [37][38][39] Family support reduces relapse and improves clinical outcomes. [40] Our instrument may not have captured the specific aspects of social support crucial for treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…schizophrenia and bipolar disorder), perceived social support improved adherence to CVD medication. There was a 4.2% increase in medication adherence for each 1% increase in social support (OR 1.04, 95% CI 1.02-1.07, P = 0.002) [92]. In an HF setting, a prospective cohort study in Taiwan showed an intimate relationship with a spouse or caregiver was associated with a lower risk of 18-month all-cause readmission and cardiac readmission.…”
Section: Social Supportmentioning
confidence: 92%
“…Whilst this can be partially attributed to SMI-related deaths including suicide, physical comorbidities are estimated to cause approximately 60% of this mortality gap (1,2). appointment attendance (19). Therefore, potential enhancements to improve physical outcomes would be to integrate an emphasis on statins and expand the potential for social support through the intervention.…”
Section: Introductionmentioning
confidence: 99%